Selecting Indicators for the Quality of Mental Health Care at the Health Systems Level in OECD Countries - Hermann, Richard (OECD Publishing, 2004)
This report presents the consensus recommendations of an international expert panel on indicators for mental health care. Using a structured review process, the panel selected a set of 12 indicators to cover the four key areas treatment, continuity of care, coordination of care, and patient outcomes. The report describes the review process and provides a detailed discussion of the scientific soundness and policy importance of the 12 indicators as follows ...
Keywords: Social Issues/Migration/Health